Determinant of Muslim women to visit "viral" places: Understanding the influence of social media, distance, and Fear of Missing Out (FoMo) - Sakti, Indra (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2023)
The study explores the relationships between social media intensity, FoMO, visit intention, and potential mediation and moderation effects of perceived distance. 186 Muslim women were involved in the study, and the data were analyzed using moderation-mediation procedures. The results reveal a substantial positive correlation between the intensity of social media use and FoMO, indicating that an increased investment of time in social media corresponds to increased FoMO levels among respondents. Moreover, a robust positive correlation was identified between the intensity of social media use and respondents' intention to visit a place and FoMO's intention to visit. The results of this research study also reveal the mediating role of FoMO and moderating perceived distance on the relationship between social media intensity and visit intention. Public interest statement The study uncovers that FoMO significantly motivates the intention to visit the place. Further scrutiny indicates that social media intensity indirectly influences the intention to visit through FoMO, revealing mediation effects. The research sets the stage for subsequent investigations aimed at a deeper understanding of the roles played by social media and FoMO in shaping tourism intentions